1997
DOI: 10.1177/019262339702500109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Data and Risk Assessment of Selected Toxic End Points of the Thyroid Gland

Abstract: Many goitrogenic xenobiotics that increase the incidence of thyroid tumors in rodents exert a direct effect on the thyroid gland to disrupt one of several possible steps in the biosynthesis, secretion, and metabolism of thyroid hormones. This includes (a) inhibition of the iodine trapping mechanism, (b) blockage of organic binding of iodine and coupling of iodothyronines to form thyroxine (T 4 ) and triiodothyronine (T 3 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
192
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(204 citation statements)
references
References 26 publications
8
192
0
4
Order By: Relevance
“…SDM exerts a goitrogenic effect by inhibition of TPO, which catalyzes a reaction essential to thyroid hormone synthesis, resulting in marked decrease in circulating T 3 and T 4 levels and compensatory increase in TSH levels as well as thyroid weights in rats (Hill et al, 1989;Capen, 1997). In the present study, SDM treatment in fact reduced serum T 3 and T 4 levels, and consequently increased serum TSH levels.…”
Section: Hormone Analysissupporting
confidence: 51%
See 2 more Smart Citations
“…SDM exerts a goitrogenic effect by inhibition of TPO, which catalyzes a reaction essential to thyroid hormone synthesis, resulting in marked decrease in circulating T 3 and T 4 levels and compensatory increase in TSH levels as well as thyroid weights in rats (Hill et al, 1989;Capen, 1997). In the present study, SDM treatment in fact reduced serum T 3 and T 4 levels, and consequently increased serum TSH levels.…”
Section: Hormone Analysissupporting
confidence: 51%
“…The other, resulting from exposure to non-genotoxic chemicals, involves the negative feedback system of the hypothalamus-pituitarythyroid. Decreased circulating T 3 or T 4 levels due to disruption of thyroid function increase TSH, by which prolonged stimulation of follicular epithelium results in thyroid neoplasia (Hill et al, 1989;McClain, 1992;Capen, 1997). Many factors may contribute to decreases in circulating thyroid hormone levels.…”
Section: Hormone Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that development of thyroid proliferative lesions initiated by pretreatment with DHPN was obviously increased by SDM validates the experimental model used in the present study. It is well documented that sulfonamides including SDM exert a goitrogenic effect by inhibition of thyroperoxidase, resulting in marked decreases in circulating T 3 and T 4 and consequent compensatory increases in TSH and thyroid weight in rats. 3) Epidemiological studies suggest that a diet rich in soy products reduces the risk of several cancers, notably those of the prostate, 10) breast, 11) uterus 12) and stomach.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds, including several flavonoids, isoflavones, lignans, phytosterols and coumestans, exert antiestrogenic effects by competitive binding to estrogen receptors. 9) Several 3 To whom correspondence should be addressed. E-mail: son@nihs.go.jp epidemiological studies have suggested that soy products and isoflavones may be protective against breast and other hormone-related cancers in humans.…”
mentioning
confidence: 99%